Two new species of Andinia (Pleurothallidinae) from the Central Cordillera of Peru - Ocupa Horna, Luis; Vieira-Uribe, Sebastián; Yupanqui Godo, Luis Enrique (Lankesteriana: International Journal on Orchidology, 2021)
Two new Andinia species are described, A. barba-caprina and A. crassipetala, both found during a botanical expedition to the montane forests of the Central Cordillera of the Peruvian Andes. They are compared with morphologically similar species, and Lankester Composite Dissection Plates (LCDP) are provided. Andinia barba-caprina is more similar to A. tingomariana but is distinguished by having obovate sepals with sparsely erose margins and the lip with narrowly obtuse, short basal lobes and a group of large hairs on the abaxial surface. Andinia crassipetala is distinguished from the two most similar species, A. hernandoi Est.Domínguez & S.Vieira-Uribe and A. persimilis (Luer & Sijm) Karremans & S.Vieira-Uribe for having thick, deltate and obtuse petals.